A self-piercing-through riveting method for joining of discontinuous carbon fiber reinforced nylon 6 composite. (1st April 2020) - Rao, Zhenghua; Ou, Liang; Wang, Yaqiong; Wang, Pei-Chung
Highlights: A novel riveting method for carbon fiber thermoplastic composites was proposed. Rivet leg pierces through workpieces and flares out along the die to create a hook. Mechanical interlock between rivet and workpieces dominated the joint strength. The increases in rivet length and pip height led to an increase in joint strength. The method serves as a peel stopper in joining of Cf/PA6 composites. Abstract: An innovative self-piercing-through riveting (SPTR) method for joining of discontinuous carbon fiber reinforced nylon 6 composite (Cf /PA6) to serve as a peel stopper has been developed. In this joining method, the leg of the rivet is forced through the workpieces and into contact with the die troughs, and the leg flares out along the trough surfaces to create a hook mechanically linking the adjacent workpieces. To develop this method, SPTR of 2.5 mm thick compression molded Cf /PA6 with 30% mass fiber and the load–displacement characteristics of the riveted lap-shear joints under a quasi-static loading were tested and modeled. The results showed that the static strength and displacement of the self-piercing-through riveted joint were significantly stronger than those of the joints made with conventional self-piercing riveting (SPR) process. These results were primarily attributed to a greater amount of materials being clinched in SPTR process with solid mechanical interlocks formed between the rivet and workpieces. Although the severe local deformation was induced next to the tip of the rivet leg during SPTR process, the mechanical interlock (i.e., undercut) between the rivet and workpieces appeared to be a dominant factor in determining the static strength of the self-piercing-through riveted Cf /PA6.